Measuring higher education services using the SERVQUAL model - Saliba, Katia (Izzivi prihodnosti, 2018)
Research Question (RQ): In this research analysis, SERVQUAL tool was used with higher education institutions (HEIs) to measure service quality as well as to compare them. HEIs were compared to see the service quality dimensions that need improvements in public HEI verses private HEIs. More specifically, to examine if there is a common trend with public universities in specific quality service dimensions that were not expected and less perceived by students. Purpose: Quality of service in a higher education institution is an essential aspect to ensure competency and attractiveness in the marketplace. Students are the primary stakeholders. Students expectations from an HEI and their perception of quality of service needs to be a strategic objective of an HEI. Public HEIs have a different strategy from private ones. In this research study, such a difference was examined to determine if it is reflected in a specific service quality dimension. Method: The study is based on a comparative literature review of SERVQUAL instrument used in measuring service quality in HEIs. Results obtained from the review of literature were triangulated and examined for specific quality dimensions that were common in public HEIs that need improvement. Results: Students perception was less than expected in the quality of service provided. Public HEIs should consider reliability and responsiveness as a priority and along with other dimensions to improve service quality. SERVQUAL could be used to examine and measure students perspective and measure periodical and implemented strategic objectives of higher education. Organization and Society: The research impact is mainly on HEIs, their managers, and their plans for quality improvements. Originality: The findings of the measuring tool SERVQUAL was compared among different HEIs from the review of literature using triangulation techniques. Limitations / Further research: Limitations of the study are concerned mostly with the different data collected among different HEIs in different geographical regions. Triangulation of the same scale excluded many related studies which used different scale measures or further specified quality dimensions yielding fewer studies that could be triangulated. Further research could be conducted by collecting data on public and private HEIs in the same region and time and then repeated at different time intervals to examine any progress.
Keywords: higher education; public HEI; service quality; SERVQUAL; strategic objectives; students expectation; students perceptions; triangulation